2020
DOI: 10.1016/j.pss.2019.104756
|View full text |Cite
|
Sign up to set email alerts
|

The effects of asteroid layering on ejecta mass-velocity distribution and implications for impact momentum transfer

Abstract: Most bodies in the Solar System do not have a homogeneous structure. Understanding the outcome of an impact into regolith layers of different properties is especially important for NASA's Double Asteroid Redirection Test (DART) and ESA's Hera missions. Here we used the iSALE shock physics code to simulate the DART impact into three different target scenarios in the strength regime: a homogeneous porous half-space; layered targets with a porous weak layer overlying a stronger bedrock; and targets with exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 65 publications
4
43
0
Order By: Relevance
“…DART will send a spacecraft that impacts Dimorphos, the secondary of the Didymos system, in 2022 (Cheng et al, 2018), to assess the DART spacecraft's deflection capability while Hera will later conduct remote sensing observations after rendezvousing with it in 2026 (Michel et al, 2020b). Studies have shown that the deflection capability strongly depends on the environments and physical properties of the target asteroid, implying that detailed analyses are necessary to employ proper asteroid deflection technologies (Agrusa et al, 2020;Hirabayashi et al, 2019aHirabayashi et al, , 2017Raducan et al, 2020Raducan et al, , 2019Stickle et al, 2020).…”
Section: Planetary Defensementioning
confidence: 99%
“…DART will send a spacecraft that impacts Dimorphos, the secondary of the Didymos system, in 2022 (Cheng et al, 2018), to assess the DART spacecraft's deflection capability while Hera will later conduct remote sensing observations after rendezvousing with it in 2026 (Michel et al, 2020b). Studies have shown that the deflection capability strongly depends on the environments and physical properties of the target asteroid, implying that detailed analyses are necessary to employ proper asteroid deflection technologies (Agrusa et al, 2020;Hirabayashi et al, 2019aHirabayashi et al, , 2017Raducan et al, 2020Raducan et al, , 2019Stickle et al, 2020).…”
Section: Planetary Defensementioning
confidence: 99%
“…Larger ejected masses and larger craters (even exceeding 100 m diameter on the 163 m diameter moon) are possible though less likely, and the precise outcome depends on the unknown strength, porosity and other physical properties of Didymoon. Other Didymoon-specific simulations of the impact show ejecta speeds approaching the impactor speed (expected to be 6 km/s, Cheng et al (2018)) in some cases, though the bulk of material is released at much lower (several to hundreds of m/s) speeds (Richardson & O'Brien 2016;Raducan et al 2019;Stickle et al 2020). We note that the cratering produced by Deep Impact proved difficult to interpret.…”
Section: Ejectamentioning
confidence: 75%
“…Previous experimental and numerical studies of impacts on layered targets showed that the greatest diversity in crater morphology caused by layering occurs when the ratio of upper layer thickness, h , to crater diameter, D , is in the range 0.08 < h / D < 0.3 (Quaide & Oberbeck, 1968; Raducan et al, 2020; Senft & Stewart, 2007). In these studies, which examined crater formation in weak regolith‐like targets, underlain by a rocky substrate, the craters exhibited four distinct morphologies depending on the h / D ratio.…”
Section: Diverse Crater Morphologies In Rock/iron Targetsmentioning
confidence: 99%